Fiscal Positions in Latin America : Have They Really Improved? - Zettelmeyer, Jeromin (IMF Working Papers; Working Paper, 2008)
Fiscal performance in Latin America looks much improved this decade compared to the 1980s or 1990s. Is this a "structural" improvement or likely to be transitory? This paper answers this question by estimating the relationship between non-commodity revenue and the economic cycle, and evaluating commodity revenues using alternative medium term commodity price projections. The main result is that structural revenues have indeed improved as a share of GDP, and structural primary balances are currently in surplus in many Latin American countries. However, the magnitude of these improvements is uncertain, in part due to uncertainty about the commodity price outlook.